Constant-Moderate and High-Intensity Interval Training Have Differential Benefits on Insulin Sensitive Tissues in High-Fat Fed Mice - Martinez-Huenchullan, Sergio F.; Ban, Linda A.; Olaya-Agudo, Luisa F.; Maharjan, Babu Raja; Williams, Paul F.; Tam, Charmaine S.; Mclennan, Susan V.; Twigg, Stephen M. (Frontiers in Physiology, 2019)
In a mouse model of diet-induced obesity, this study determined if two exercise prescriptions with equivalent time and distance covered, (constant-moderate endurance (END) and high intensity interval training (HIIT)), exert differential metabolic benefits on insulin sensitive tissues. Male 10 wk old C57BL/6 mice were fed a high fat diet (HFD; 45% kcal fat) ad libitum for 10 wks and for a further 10 wks they underwent END or HIIT training (3x40min sessions/wk). Untrained HFD and chow-fed mice acted as controls. At 30 wks of age, mice were sacrificed and quadriceps muscle, subcutaneous adipose tissue (SAT) and liver were excised. Neither END nor HIIT altered body weight or composition in HFD mice. In quadriceps, HFD decreased high-molecular weight adiponectin protein, which was normalized by END and HIIT. In contrast, HIIT but not END reversed the HFD-driven decrease in the adiponectin receptor 1 (AdipoR1). In SAT, both programs tended to decrease collagen VI protein (p=0.07-0.08) in HFD, whereas only HIIT induced an increase in the mRNA (3-fold vs HFD untrained) and protein (2-fold vs HFD untrained) of UCP1. In liver, only END reversed collagen I accumulation seen in HFD untrained mice. Our results suggest that HIIT may promote better systemic metabolic changes, compared to END, which may be the result of the normalization of muscle AdipoR1 and increased UCP1 seen in SAT. However, END was more effective in normalizing liver changes, suggesting differential metabolic effects of END and HIIT in different tissues during obesity.